E3 Ubiquitin Ligases: Potential Therapeutic Targets for Skeletal Pathology and Degeneration. (27th September 2022) - Zeng, Ruiyin; Xiong, Yuan; Lin, Ze; Panayi, Adriana C.; Sun, Yun; Cao, Faqi; Liu, Guohui
Abstract : The ubiquitination-proteasome system (UPS) is crucial in regulating a variety of cellular processes including proliferation, differentiation, and survival. Ubiquitin protein ligase E3 is the most critical molecule in the UPS system. Dysregulation of the UPS system is associated with many conditions. Over the past few decades, there have been an increasing number of studies focusing on the UPS system and how it affects bone metabolism. Multiple E3 ubiquitin ligases have been found to mediate osteogenesis or osteolysis through a variety of pathways. In this review, we describe the mechanisms of UPS, especially E3 ubiquitin ligases on bone metabolism. To date, many E3 ubiquitin ligases have been found to regulate osteogenesis or osteoclast differentiation. We review the classification of these E3 enzymes and the mechanisms that influence upstream and downstream molecules and transduction pathways. Finally, this paper reviews the discovery of the relevant UPS inhibitors, drug molecules, and noncoding RNAs so far and prospects the future research and treatment.